2019
DOI: 10.3390/f10060514
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Growth Responses to Increasing Drought of an Endangered Tree Species in Southwest China

Abstract: Research Highlights: We compared annually resolved records of tree-ring width and stable isotope of dead and surviving Fokienia hodginsii (Dunn) Henry et Thomas trees. We provide new insights into the relationships and sensitivity of tree growth to past and current climate, and explored the underlying mechanism of drought-induced mortality in F. hodginsii. Background and Objectives: Drought-induced tree decline and mortality are increasing in many regions around the world. Despite the high number of studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In some evergreen tree species, chronic water stress and prolonged stomatal closure will lead to a reduced photosynthesis, resulting in a further decrease in stored carbon as respiration continues (Zheng et al . 2019). Carbohydrate reserves can be then further reduced as are required to drive phloem transport, maintain turgor, and refill embolized xylem during drought (McDowell et al .…”
Section: Resilience and Adaptation Of Tunisian Forests To Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…In some evergreen tree species, chronic water stress and prolonged stomatal closure will lead to a reduced photosynthesis, resulting in a further decrease in stored carbon as respiration continues (Zheng et al . 2019). Carbohydrate reserves can be then further reduced as are required to drive phloem transport, maintain turgor, and refill embolized xylem during drought (McDowell et al .…”
Section: Resilience and Adaptation Of Tunisian Forests To Climate Changementioning
confidence: 99%
“…Drought-induced tree decline and mortality are increasing in many regions around the world, which will fundamentally alter forest composition (Engelbrecht et al 2007;Zheng et al 2019), structure (Allen et al 2010), and biogeography (D'Orangeville et al 2016). To develop mitigation strategies and maintain forest sustainability and productivity, it is important to understand how forest species will respond to severe droughts.…”
Section: Climate Change Imprints In Dendrochronological and Phenologi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Over 1/2 of the mountainous area in southern China is covered in harsh woodland vegetation, a habitat type that is highly suitable for planting with F. hodginsii given its stronger soil improvement ability than other cultivated tree species in southern China. It was recently documented that both human disturbance [11] and global warming [12] are changing the present status of F. hodginsii by hastening the degradation and fragmentation of its native habitat, which impairs regeneration of F. hodginsii stands in natural forest sites [13]. Thus, establishing seed orchards is imperative for the protection as well as application of F. hodginsii [14].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of decreasing growth rates after the 1980s has been reported also in Asia. In this issue, Zheng et al [9] showed how Fokienia hodginsii, an endanger conifer, has decreased its growth, increased the frequency of missing rings, and experimented an unprecedented increase in sensitivity of 13 C and radial growth to drought, likely related to increasingly dry conditions. These researchers linked these negative effects to a spike in tree mortality, which may have resulted from diminished carbon fixation and water availability.…”
mentioning
confidence: 99%